Geometric performance of a camera with single sensor and multiple heads - Tommaselli, A. M.G. [UNESP]; Berveglieri, A. [UNESP]; Imai, N. N. [UNESP]; Santos, G. H. [UNESP]; Moriya, E. A.S. [UNESP]; Watanabe, F. S.Y. [UNESP]; Salvador Neto, L. (Copernicus Publications, 2020)
Remote sensing with lightweight optical sensors is becoming a powerful tool to solve many problems in agriculture. Achieving the level of spatial and spectral resolutions required for this type of detection at an acceptable cost-benefit ratio has motivated the development of new sensors which must be lightweight to be carried by mobile robots either aerial or terrestrial. One new type of multiple head cameras has been developed by Agrowing, an Israeli company developing technology for digital agriculture. The aim of this paper is to analyse the geometric features of an Agrowing dual head camera trough calibration experiments. The sensor was calibrated following two options, depending on the cropping technique used to produce the 4 spectral bands. Different calibration techniques were also used and very accurate results were achieved. Experiments with data collected with a UAV also confirmed the results achieved with close range calibration.
Keywords: camera calibration; dual head sensor; Multispectral camera